CONCEPTUAL FUNDAMENTALS OF MODERN TECHNOLOGY OF TEACHING ASTRONOMY IN GENERAL SECONDARY SCHOOLS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article discusses the conceptual foundations of modern pedagogical technologies for teaching astronomy in secondary schools.